Cream Puff Mocaf dan Tepung Umbi Garut (Maranta arundinacea): Pengembangan Dessert Sumber Zat Besi dalam Pemanfaatan Pangan Lokal - Nurhidayati, Vieta Annisa; Lestari, Fanisa Dwi (LPPM Universitas Negeri Jakarta, 2025)
of the resulting cream puff can be improved by adding arrowroot flour. This study aimed to develop cream puffs made from mocaf and arrowroot flour, filled with pastry cream enriched with red beans as a source of iron. The study employed a completely randomized design with one factor and three treatments. The research was conducted from February to April 2024. The combinations of mocaf and arrowroot flour used were F1 (80:20), F2 (85:15), and F3 (90:10). The results showed that formula F3 was selected based on the exponential comparison method. Each serving of the cream puff product from the selected formula contributes 15.2% of the daily iron requirement for adolescent girls aged 16–18 and women aged 19–29, and contributes 22% of the daily value for iron for the general population, making it a pastry product rich in iron.